The relationship between board characteristics and Malaysian firm performance / Maliza Mohd Nor - Mohd Nor, Maliza (2011)
This study attempt to analyze the trend of board characteristics and try to investigate the relationship of board characteristics and Malaysian firm performance focusing on the elements of board size, proportion of independent non-executive directors, duality role and board gender diversity. In addition, firm size and leverage have been included to control other influential factors. The data are gathered from the analysis of companies' annual report for a sample of 169 companies over a period of 2009 and 2010. The study employs hierarchical multiple regression analyses. The preliminary results of this study reveal most of Malaysian companies have complied with the recommendation of the MCCG (2000) and MCCG (2007) Code to have an effective of board structure and there is a significant relationship between board sizes to firm performance. In addition, it provides into which there are no association between proportion of independent non-executive directors, duality role and board gender diversity to firm performance.